Elaboración de un mapa geomorfológico a escala 1:25000, de la parroquia rural San Pedro de la Bendita, perteneciente al cantón Catamayo, provincia de Loja, Ecuador. - Guaman Alejandro, Stalin Serafin (2022)
Nowadays, the use of Geographic Information Systems (GIS) as cartographic tools has been growing and the use of these tools for land management and analysis is becoming more and more evident. Under this point of view and taking into account that for land planning it is necessary to have updated geoinformation, precise location and a correct classification of the geomorphological features for a quick interpretation and representation of the attributes of the areas of interest. For the San Pedro de la Bendita parish, the generation of this updated and reliable information at a scale of 1:25 000 is very important, and for this reason the present work proposes the elaboration of a geomorphological map at a scale of 1:25 000, of the rural parish of San Pedro de la Bendita, belonging to the Catamayo canton, province of Loja, Ecuador. This map of geomorphological units is based on the methodology proposed by the MAE in 2013, where a quantitative geomorphology is studied, which describes the three-dimensional bodies with their shape, size, volume and characteristic topography, namely, the elements that generate a relief starting from the analysis of macorelief and mesorelief. In this methodology, the definition, modeling, delineation and visualization of geomorphological units was carried out, in addition to the topographic indexes (shading, slope, curvature in profile, in plan, longitudinal, transversal and maximum and minimum curvature) to later add the digital terrain model, thus having an automatic Unsupervised Isodata classification, through semi-automatic techniques of the ENVI 5.3 software, this result is improved with the application of filters that allowed improving the definition of the morphometry of the study area. Finally, it is complemented with information on land use, slopes, geology, 3D interpretation, validations and field revalidations, resulting in the geomorphological map of the study area. Key words: Geomorphology, Digital Terrain Model, Geoforms, Catamayo, San Pedro de la Bendita.